SP1.1.17The relationship between colorectal neoplasia and body composition in a bowel screening population. (28th October 2021) - Di Rollo, Domenic; Morton, Christopher; McMillan, Donald; Horgan, Paul; Mansouri, David
Abstract: Aims: Conflicting evidence exists as to the effect of elevated BMI in the development of colorectal neoplasia. Yet BMI is a crude measure of adiposity. The present study investigates the association between CT derived measures of body composition including sarcopenia, subcutaneous fat index (SFI) and visceral obesity and colorectal neoplasia. Methods: 358 consecutive patients undergoing CT virtual colonoscopy (CTC) as part of the Scottish Bowel Screening Programme were eligible for inclusion. Demographic data and the above measures body composition were calculated using previously published CT derived methods. Medical records were examined for colonoscopic findings and pathology reports. Results: 121/358 (34%) were males. Median age 65. 126/358 (35%) patients were found to have a colorectal neoplasia. 84/126 (67%) had advanced neoplasia. 26/358 (7%) had adenocarcinoma. On multivariable analysis, both male sex and visceral obesity was associated with the presence of colorectal neoplasia, OR 2.62, [95% CI 1.51-4.55, p = 0.001] and OR 2.83, {95% CI 1.25-6.41, p = 0.01] respectively. The relationship was dose dependent with an increased risk of colorectal neoplasia in the 3rd [OR 2.13 95% CI 1.09-4.14 p < 0.05] and 4th [OR 3.77 95% CI 1.96-7.26 p < 0.001] quartiles of visceral fat area. BMI, SFI and sarcopenia were not associated with colorectal neoplasia in the present study. Conclusions: Male sex and in particular, visceral obesity is associated with increased risk of colorectal neoplasia. In addition to the known cardiovascular and metabolic dangers of visceral obesity, the present work suggests that visceral obesity may also play a role in colorectal neoplasia formation.